Comparison of free fatty acid content of human milk from Taiwanese mothers and infant formula - Chih-Kuang Chuang; Chun-Yan Yeung; Wai-Tim Jim; Shuan-Pei Lin; Tuen-Jen Wang; Sung-Fa Huang; Hsuan-Liang Liu (Elsevier, 2013)
Objective: Few studies on the free fatty acid (FFA) content of milk from non-Caucasian mothers have been published. We compared the FFA concentrations in human milk (HM) from Taiwanese mothers of preterm (PTHM) and full-term infants (FTHM) and in infant formula (IF). Materials and methods: Thirty-eight HM samples were collected from 23 healthy lactating mothers and 15 mothers who gave birth prematurely (range 29-35 weeks, mean 33 weeks). The regular formula and preterm infant formula (PTIF) for three brands of powdered IF were also evaluated. Milk samples were extracted and methylated for analysis by gas chromatography/mass spectrometry (GC/MS). Results: Reference values for individual FFAs in breast milk from Taiwanese mothers were determined. The mean total FFAs were significantly higher in IF (21,554 μmol/L) and PTIF (19,836 μmol/L) than in FTHM (8,540 μmol/L) and PTHM (9,259 μmol/L) (p < 0.05). Saturated FAs were predominant in all types of milk (43.1% for FTHM, 42.8% for PTHM, 45.5% for IF and 45.3% for PTIF). Monounsaturated FAs were significantly higher in IF and PTIF (42.6% and 43.9%) than in FTHM and PTHM (37.7% and 39.5%), and polyunsaturated FAs in FTHM and PTHM (20% and 18.2%) were higher than in IF and PTIF (11.9% and 10.9%). HM had a more desirable linoleic acid/α-linolenic acid ratio than IF. No significant differences in individual FFAs in FTHM were observed among three lactating periods. Conclusion: FFA levels in HM from Taiwanese mothers are in agreement with results for different geographically distinct populations. Nevertheless, the FFA content in IF did not meet well with HM, particularly, the excess additives of saturated and monounsaturated FAs, and the shortage of polyunsaturated FAs. The effect of variations in FFA content in IF on future unfavorable outcomes such as obesity, atopic syndrome, and less optimal infant neurodevelopment should be further investigated.